Penguatan Literasi Pendidikan Anti Korupsi bagi Komunitas SSQ Holistik Internasional melalui Kegiatan Webinar Pengabdian Masyarakat : Pengabdian - Eko Sudarmanto; Nikem Kurnia Ningsih; Zakiyah Zakiyah; Irwan Irawadi Barus; Hendi Herdiansyah; Asep Suhendar; Rr Anggraini Soemadi; Sitti Rabiah Yusuf (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Corruption is a serious issue that affects various aspects of social life, economic development, and institutional governance, thus requiring preventive efforts that are not only repressive but also educational in nature. This community service activity aims to strengthen anti-corruption education literacy among members of the SSQ Holistic International (SSQ-HI) community through a webinar-based learning approach. The implementation method employed an educative–interactive approach, including material presentations, reflective discussions, and evaluations of participants’ understanding. The activity involved SSQ-HI community members and participants from the general public with diverse educational backgrounds. The results indicate an improvement in participants’ understanding of anti-corruption education literacy as the capacity to comprehend, analyze, and make decisions based on the values of integrity, honesty, and responsibility. The novelty of this activity lies in the integration of literacy concepts with anti-corruption education through a collaborative and interdisciplinary non-formal community education approach. This approach proved effective in fostering critical awareness and strengthening the internalization of anti-corruption values in everyday life. The activity implies that strengthening anti-corruption education literacy through community-based initiatives can serve as a sustainable preventive education model for fostering a culture of integrity in society.